2006
DOI: 10.1167/iovs.06-0036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Latanoprost on the Expression of Matrix Metalloproteinases and Their Tissue Inhibitors in Human Trabecular Meshwork Cells

Abstract: Contrary to the expected result, latanoprost seems to have a significant effect on TM cells. The transcription of the genes for MMP-1, -3, -17, and -24 is increased by latanoprost treatment. TIMP-2, -3, and -4 are also upregulated. The upregulation of these TIMPs may compensate for the increase of those MMPs. The absence of MMP-9 and concurrent upregulation of a greater number of TIMPs may explain the limited effect of latanoprost on TM outflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 42 publications
5
68
0
3
Order By: Relevance
“…Morphological changes are not restricted to the anterior portion of the ciliary body; they also occur in the trabecular meshwork (Richter et al, 2003). It is not surprising, therefore, that tissue inhibitor of metalloproteinases and matrix metallopeptidase regulation occurs in trabecular meshwork cells (Oh et al, 2006). Gene regulation associated with FP receptor stimulation, however, is not identical in ciliary muscle and trabecular meshwork with respect to genes that would influence aqueous humor dynamics (Zhao et al, 2003).…”
Section: Fp Receptorsmentioning
confidence: 99%
“…Morphological changes are not restricted to the anterior portion of the ciliary body; they also occur in the trabecular meshwork (Richter et al, 2003). It is not surprising, therefore, that tissue inhibitor of metalloproteinases and matrix metallopeptidase regulation occurs in trabecular meshwork cells (Oh et al, 2006). Gene regulation associated with FP receptor stimulation, however, is not identical in ciliary muscle and trabecular meshwork with respect to genes that would influence aqueous humor dynamics (Zhao et al, 2003).…”
Section: Fp Receptorsmentioning
confidence: 99%
“…The MMP group of proteinases is secreted extracellularly in their inactive form, and require further processing for activation [86,87]. MMPs are constitutively expressed throughout the TM, expression profiles responding to various stimuli [88][89][90]. Tight regulation of proteinase expression within the ECM is required for effective control of outflow resistance.…”
Section: Modulation Of Ecm Turnovermentioning
confidence: 99%
“…Extensive studies have demonstrated prostaglandin-related decreases in TM cell contractility and outflow resistance of organ-cultured anterior segments [121][122][123]. The overall mechanisms through which prostaglandins enhance AH outflow remain to be fully elucidated; however, it is widely accepted that remodeling of the ECM plays a part [124][125][126][127], and it is of note that upregulation in MMP expression, through activation of prostaglandin receptors, may be involved [89,128]. However, the unique receptor profile for each analog may induce ECM modulation via different cascade pathways.…”
Section: Traditional Topical Medications In the Management Of Glaucomamentioning
confidence: 99%
“…However, topical prostaglandin analogues are believed to achieve pressurelowering effects by increasing uveoscleral outflow without any effect on aqueous humour production (Toris et al, 1993). However, their effect on the trabecular meshwork remains unclear (Oh et al, 2006;Johnson et al, 2010). There was no statistically significant difference in efficacy between the 3 commercially available topical prostaglandin analogues but there was a reported borderline increased incidence of ocular hyperaemia with bimatoprost (van Not available for patient use www.intechopen.com de Valk et al, 2005;Zimmerman et al, 2009).…”
Section: Prostaglandin Analoguesmentioning
confidence: 99%
“…The vasodilatation effect of latanoprost, although minimal, is also postulated to play a role in facilitating uveoscleral outflow. Although increases aqueous outflow through non-conventional pathways seems to be responsible for the pressure-lowering effect of latanoprost, there are ongoing studies providing evidence of the possible role of trabecular meshwork outflow (Oh et al, 2006). In spite of uncertainty in the mechanism of latanoprost action, latanoprost is a clinically proven efficacious topical anti-glaucoma drug.…”
Section: Topical Latanoprost 0005%mentioning
confidence: 99%